Association between exclusive breastfeeding and stunting among toddlers in a high-burden rural community of South Central Timor: a cross-sectional study - Roslin E. M. Sormin; Emanuel Gerald Alan Rahmat (International Journal of Public Health Science (IJPHS), 2026)
This cross-sectional study assessed the relationship between exclusive breastfeeding and stunting among toddlers in Batuputih, South-Central Timor, East Nusa Tenggara, Indonesia. Conducted in July 2025, it involved 52 children aged 6-59 months using total sampling. Exclusive breastfeeding history was obtained through caregiver interviews and verified with health records to reduce recall bias. Height-for-age z-scores were measured using WHO standards, and data were analyzed with Fisher’s exact test and penalized logistic regression with Firth correction to address the small sample size. Stunting prevalence was 59.6%, while exclusive breastfeeding coverage reached 82.7%. All toddlers who were not exclusively breastfed were stunted. Regression analysis confirmed a strong protective effect of exclusive breastfeeding against stunting (OR 0.05; 95% CI 0.003-0.92; p = 0.012), which remained significant after adjusting for birth weight, sex, recent illness, and maternal education. These findings highlight exclusive breastfeeding as a critical protective factor in high-burden rural settings. Yet, the persistence of stunting despite high coverage underscores the need for integrated strategies at the primary health-care and district levels. Strengthening breastfeeding counseling must be complemented by maternal nutrition, infection prevention, and sanitation improvements within broader stunting prevention frameworks tailored to rural Timorese communities.